Virtual Screening and Bioactivity Evaluation of Novel Androgen Receptor Antagonists From Anti-PCa Traditional Chinese Medicine Prescriptions - Han, Wenya; Shi, Yuqi; Su, Jie; Zhao, Zhennan; Wang, Xin; Li, Jiazhong; Liu, Huanxiang (Frontiers in Chemistry, 2020)
Prostate cancer (PCa), a type of malignancy that arises in the prostate gland, is the most commonly diagnosed neoplasm and the second leading cause of cancer-related deaths in men. Acquisition of resistance to conventional therapy is a major problem for PCa patient treatment. Androgen receptor (AR) signaling pathway is necessary in the pathogenesis of prostate cancer, and there is a heightened interest in finding novel AR antagonists that target AR and its regulatory pathways. In our search for novel androgen receptor antagonists, we focus on the Traditional Chinese Medicine (TCM), which has been used for thousands of years to prove effective in the treatment of cancer. In this study, we collected 653 traditional Chinese medicine prescriptions that have certain therapeutic effect to prostate cancer, including the prescriptions and even the folk prescriptions. After summarizing the frequency of herbs and gathering the natural products contained in these prescriptions, we built a natural products database to do computer-aided virtual screening and drug-like evaluation to find potential AR antagonists. Totally 25 compounds were submitted to experimental biological activity tests. Through the MTT cell proliferation experiment, 5 chemicals were found to inhibit the proliferation of LNCaP cells in a concentration-dependent manner. Especially, MoL_11 was found to have good antagonistic activity and significantly inhibit fluorescence enzyme activity by the AR reporter gene experiment. Finally, the molecular dynamics simulation method was used to study the interaction between the most active compound MoL_11 and the wild-type and F876L mutant androgen receptor (WT / F876L AR), and it was found that F876L AR could not cause resistance to MoL_11.